First measurement of the CP-violating phase in B0s→J/ψ( →e+e−)ϕ decays; The European Physical Journal C; Vol. 81, iss. 11 - Aaij R. Roel; Beteta C. B. Carlos Abellan; Eydelman S. I. Semen Isaakovich; Kharisova A. E. Anastasiya Evgenjevna; Panshin G. L. Gennady Leonidovich (2021, 2021)
Title screen